2021
DOI: 10.1002/jbt.22913
|View full text |Cite
|
Sign up to set email alerts
|

Pyridostigmine bromide, chlorpyrifos, and DEET combined Gulf War exposure insult depresses mitochondrial function in neuroblastoma cells

Abstract: Gulf War Illness (GWI) is defined by the Centers for Disease Control and Prevention (CDC) as a multi-symptom illness having at least one symptom from two of three factors, which include: fatigue, mood-cognition problems, and musculoskeletal disorders. The cluster of long-term symptoms is unique to military personnel from coalition countries including United States, Australia, and the United Kingdom that served in Operation Desert Storm from 1990 to 1991. Reporting of these symptoms is much lower among soldiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Delic et al . [ 72 ], using a neuronal cell culture model, found that combined exposure to N,N-diethyl-meta-toluamide (DEET), chlorpyrifos, and PB (a combination intended to mimic veterans’ exposure in the GW) caused a large decrease in mitochondrial spare respiratory capacity in 4 hours, at exposure levels that did not affect cell viability at either 4 or 8 hours. Yates et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delic et al . [ 72 ], using a neuronal cell culture model, found that combined exposure to N,N-diethyl-meta-toluamide (DEET), chlorpyrifos, and PB (a combination intended to mimic veterans’ exposure in the GW) caused a large decrease in mitochondrial spare respiratory capacity in 4 hours, at exposure levels that did not affect cell viability at either 4 or 8 hours. Yates et al .…”
Section: Discussionmentioning
confidence: 99%
“…They are also consistent with recent work in cell culture models. Delic et al [72], using a neuronal cell culture model, found that combined exposure to N,N-diethyl-metatoluamide (DEET), chlorpyrifos, and PB (a combination intended to mimic veterans' exposure in the GW) caused a large decrease in mitochondrial spare respiratory capacity in 4 hours, at exposure levels that did not affect cell viability at either 4 or 8 hours. Yates et al [73] differentiated induced pluripotent stem cells derived from veterans with or without GWI into forebrain glutamatergic neurons, and exposed them to diisopropylflurophosphate (an organophosphate pesticide used as a sarin mimic) and cortisol (to mimic stress); this cellular model of GWI reduced cellular energetics measured as produced reducing power and mitochondrial membrane potential.…”
Section: Plos Onementioning
confidence: 99%
“…Many pharmacological studies have been performed to characterize the different responses to treatment with W. somnifera extract. Oxidative stress that can affect mitochondria is a characteristic of Gulf War exposures ( Chen et al, 2017 ; Shetty et al, 2017 ; Delic et al, 2021 ). Rats that received intraperitoneal injection of W. somnifera root extract after rotenone-induced oxidative stress had similar levels of antioxidants and lipid peroxidation to non-stress controls, demonstrating the anti-oxidative properties of W. somnifera ( Epuri et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are also consistent with recent work in cell culture models. Delic et al [78], using a neuronal cell culture model, found that combined exposure to N,N-diethyl-meta-toluamide (DEET), chlorpyrifos, and PB (a combination intended to mimic veterans' exposure in the GW) caused a large decrease in mitochondrial spare respiratory capacity in 4 hours, at exposure levels that did not affect cell viability at either 4 or 8 hours. Yates et al [79] differentiated induced pluripotent stem cells derived from veterans with or without GWI into forebrain glutamatergic neurons, and exposed them to diisopropylflurophosphate (an organophosphate pesticide used as a sarin mimic) and cortisol (to mimic stress); this cellular model of GWI reduced cellular energetics measured as produced reducing power and mitochondrial membrane potential.…”
Section: Relationship Of Chemical Exposures To Mitochondrial Parametersmentioning
confidence: 99%